Effect of SBS Polymer and Anti-stripping Agents on the Moisture Susceptibility of Hot and Warm Mix Asphalt Mixtures - Hamed Omrani; Ali Reza Ghanizadeh; Amin Tanakizadeh (Salehan Institute of Higher Education, 2017)
The primary objective of this study is exploring the moisture susceptibility of unmodified and SBS-modified hot and warm mix asphalt mixtures. To this end, two different WMA additives including Aspha-min and Sasobit were employed to fabricate WMA specimens. The moisture susceptibility of warm polymer modified asphalt (WPMA) mixes was evaluated using modified Lottman test at 25°C according to AASHTO standard (T 283). In addition, the effect of different percentages of hydrated lime (from 0% to 2%) and Zycosoil (from 0% to 0.1%) as anti-stripping additives on the moisture susceptibility of the mixtures was explored. Based on the ITS test results, WPMA prepared with Sasobit additive and polymer modified asphalt (PMA) mixes satisfied the desirable tensile strength ratio (TSR) (above 80%) but Aspha-min WPMA mixes had TSR lower than 80%.